Maritime Spatial Planning past, present, future - Zaucha, Jacek; Gee, Kira.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book is open access under a CC BY 4.0 license Maritime or marine spatial planning has gained increasing prominence as an integrated, common-sense approach to promoting sustainable maritime development. A growing number of countries are engaged in preparing and implementing maritime spatial plans: however, questions are emerging from the growing body of MSP experience. How can maritime spatial planning deal with a complex and dynamic environment such as the sea? How can MSP be embedded in multiple levels of governance across regional and national borders - and how far does the environment benefit from this new approach? This open access book is the first comprehensive overview of maritime spatial planning. Situated at the intersection between theory and practice, the volume draws together several strands of interdisciplinary research, reflecting on the history of MSP as well as examining current practice and looking towards the future. The authors and contributors examine MSP from disciplines as diverse as geography, urban planning, political science, natural science, sociology and education; reflecting the growing critical engagement with MSP in many academic fields. This innovative and pioneering volume will be of interest and value to students and scholars of maritime spatial planning, as well as planners and practitioners. Jacek Zaucha is Professor of Economics at Gdánsk University, Poland. He is long experienced in maritime spatial planning, and is currently leading the team preparing the first plan for Polish waters. Kira Gee is Research Associate at the Centre for Materials and Coastal Research (Helmholtz-Zentrum Geesthacht), Germany. She has been involved in MSP research and practice for over 20 years, and has participated in numerous national and transnational European MSP projects.
Chapter 1. Marine Spatial Planning at the interface of planning, geography and social sciences; Charles Ehler, Jacek Zaucha, Kira Gee -- Chapter 2. The ocean perspective; Kira Gee -- Chapter 3. Challenges and opportunities for ecosystem based management and Marine Spatial Planning in the Irish Sea; Tim O'Higgins, Linda O'Higgins, Anne Marie O'Hagan, Joseph Owona Ansong -- Chapter 4. Systematic conservation planning as a tool to advance ecologically or biologically significant area and marine spatial planning processes; Linda R. Harris, Stephen Holness, Gunnar Finke, Stephen Kirkman and Kerry Sink -- Chapter 5 Can Classical Location Theory Apply To Sea Space?; Jacek Zaucha -- Chapter 6. Marine spatial planning the EU's Blue Growth Policy: Past, present and future perspectives -- Angela Schultz-Zehden, Barbara Weig, Ivana Lukic -- Chapter 7. The socio-cultural dimensions of Marine Spatial Planning; Emma McKinley, Tim Acott and Tim Stojanovic -- Chapter 8. Adding people to the sea: conceptualising social sustainability in MSP; Fred Saunders, Michael Gilek and Ralph Tafon -- Chapter 9. Politics and Power in Marine Spatial Planning; Wesley Flannery, Jane Clarke and Benedict McAteer -- Chapter 10. Towards a ladder of MSP participation -- Andrea Morf, Michael Kull, Joanna Piwowarczyk, Kira Gee -- Chapter 11. Taking account of land-Sea interactions in MSP; Sue Kidd, Hannah Jones and Stephen Jay -- Chapter 12. Linking ICZM to MSP: The Mediterranean experience; Emiliano Ramieri, Martina Bocci and Marina Markovic -- Chapter 13. Stakeholder Processes in Marine Spatial Planning:Ambitions and Realities from the European Atlantic Experience; Sarah Twomey and Cathal O'Mahony -- Chapter 14. Scenario-Building for Marine Spatial Planning; Lynne McGowan, Stephen Jay, and Sue Kidd -- Chapter 15. MSP as a form of risk governance; Roland Cormier and Andreas Kannen -- Chapter 16. The Role of the Law of the Sea in Marine Spatial Planning; Dorota Pyć -- Chapter 17. The need for Marine SpatialPlanning in Areas Beyond National Jurisdiction; Susanne Altvater, Ruth Fletcher and Cristian Passarello -- Chapter 18. Evaluation of MSP - valuing the process, knowing the impacts; Riku Varjopuro -- Chapter 19. Education and Training for Maritime Spatial Planners; Helena Calado, Catarina Fonseca, Joseph Onwona Ansong, Manuel Frias and Marta Vergílio. .
Keywords: Human geography; Physical geography; Water; Hydrology; Geographic information systems; Environmental management; Environmental Law; Human Geography; Physical Geography; Water; Geographical Information System; Environmental Management; Environmental Law